Interpersonal vs. supportive group psychotherapy for depression attributed to work stress: study protocol of the multicentre, cluster-randomised, controlled IPT-Work trial - Schramm, Elisabeth; Elsaeßer, Moritz; Zehender, Nadine; Reif, Andreas; Lahmann, Claas; Feuchtinger, Manon; Deuschle, Michael; Kahl, Kai G.; Hillert, Andreas; Thiel, Nicola; Piosczyk, Hannah; Mack, Simon; et al. (BMC psychiatry, 2025)
Depression associated with occupational stress is highly prevalent, causing high rates of sick leave and thus posing significant societal and economic burden. Meta-analyses of the few studies on psychological and work-focused interventions for common mental disorders including depression report small effects on depressive symptomatology and occupational outcomes. There is an urgent need for more controlled studies on work-directed interventions assessing work outcomes. This is an interventional, multicentre, active-controlled, cluster-randomised, observer-blinded clinical trial with two parallel groups conducted in 6 clinical centres throughout Germany over the course of 3 years. A sample of 144 outpatients with work stress related depression will be cluster-randomised to either a specific interpersonal group intervention for depression and work stress (IPT-Work) or a nonspecific supportive group psychotherapy (SP). Each group consists of 10 sessions over 8 weeks of 90 min duration with 4-6 participants. Patients will be assessed at baseline, post-treatment and at 3 months follow-up. The primary endpoint is the relative change in HRSD-24 score from baseline to follow-up 3 months after end of treatment. Secondary outcome measures include the Occupational Depression Inventory (ODI), the Work Ability Index (WAI), the Return to Work Attitude (RTW-SE), the Effort-Reward-Imbalance (ERI), the Job Content Questionnaire 2 (JCQ2), and the Connor-Davidson Resilience Scale (CD-RISC). In addition, Quality of Life (WHOQOL-BREF) and days of sick leave throughout the study period will be assessed. Effects of treatment will be analysed with a linear mixed model for repeated measures including randomised arm, time point and their interaction as well as HRSD-24 baseline scores and their interaction with time point as fixed effects. Results will provide a comparison of a nonwork-directed psychological intervention and a specific, work-directed approach with respect to symptom improvement and increase in work ability. The aim is to improve quality of mental health care for depressed employees to facilitate recovery, improve work ability, and reduce the risk of long-term occupational incapacity. Ultimately, findings will inform the practice of the efficiency of using psychological group treatment in depressed individuals with work stress. German Clinical Trials Register (DRKS00035259); prospectively registered on 15th January 2025.